Deleterious Effect of High-Fat Diet on Skeletal Muscle Performance Is Prevented by High-Protein Intake in Adult Rats but Not in Old Rats - Poggiogalle, Eleonora; Rossignon, Fanny; Carayon, Aude; Capel, Fréderic; Rigaudière, Jean-Paul; De Saint Vincent, Sarah; Le-Bacquer, Olivier; Salles, Jérôme; Giraudet, Christophe; Patrac, Véronique; Lebecque, Patrice; Walrand, Stéphane; et al. (Frontiers in Physiology, 2022)
The phenotype of sarcopenic obesity is frequently associated with impaired muscle strength and performance. Ectopic lipid deposition may interfere with muscle anabolic response especially during aging. Evidence is scarce concerning the potential interplay among aging and nutrient imbalance on skeletal muscle functionality. The objective of the present study was to investigate the impact of protein intake in the context of an obesogenic diet on skeletal muscle functional properties and intramuscular lipid infiltration. Two groups of forty-two adult and thirty-seven old male Wistar rats were randomly divided into four groups: isocaloric standard diet (12% protein, 14% lipid, as ST12); isocaloric standard (high-protein) diet (25% protein, 14% lipid, ST25); hypercaloric high-fat (normal-protein) diet (12% protein, 45% lipid, HF12); and hypercaloric high-fat (high-protein) diet (25% protein, 45% lipid, HF25). The nutritional intervention lasted 10 weeks. Total body composition was measured through Echo-MRI. Lipids were extracted from tibialis anterior muscle and analyzed by gas-liquid chromatography. The functional properties of the plantarflexor muscles were evaluated in vivo on an isokinetic dynamometer. Maximal torque was assessed from the torque-frequency relationship in isometric condition and maximal power was evaluated from the torque-velocity relationship in concentric condition. In adult rats high-protein intake combined with high-fat diet determined a lower decrease in relative isometric torque, normalized to either FFM or body weight, compared with adult rats fed a high-fat normal-protein diet. High-fat diet was also detrimental to relative muscle power, as normalized to body weight, that decreased to a larger extent in adult rats fed a high-fat normal-protein diet than their counterparts fed a normal- fat, high-protein diet. The effect of high-fat diet observed in adults, with the enhanced protein intake (25%) conferring some kind of protection against the negative effects of HFD, may be linked to the reduced intramuscular fat in this group, which may have contributed to preserve, at least partly, the contractile properties. A potential role for high-protein diet in preventing ectopic lipid deposition needs to be explored in future research. Detrimental effects of high- fat diet on skeletal muscle performance are mitigated by high- protein intake in adult rats but not in old rats.